2011
DOI: 10.1007/s11661-011-0878-6
|View full text |Cite
|
Sign up to set email alerts
|

Bonding Interface Formation between Mg Alloy and Steel by Liquid-phase Bonding using the Ag Interlayer

Abstract: MASAKI KOBA, TOSHIO ARAKI, SHOICHI NAMBU, JUNYA INOUE, and TOSHIHIKO KOSEKI Liquid-phase bonding between a Mg alloy (AZ31) and low-carbon steel was attempted at 773 K (500°C) using Ag as an interlayer that forms a eutectic melt with the Mg alloy at this temperature. On the AZ31 side, eutectic melting and subsequent isothermal solidification were observed, and it was confirmed that the solidification of the eutectic liquid was promoted by the diffusion of Ag into the AZ31 base metal. On the steel side, Al was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Metallurgically, such LMCs pose less of a challenge at their interface with iron and its alloys than do aluminium alloys: Refs. [17,22,23] give examples of interfacial engineering in magnesium-steel LMCs produced by reactive transient liquid phase bonding, or by pressure infiltration, respectively. On the other hand the wet corrosion resistance of this LMC is dismal: to be usable it must be completely sealed from the environment with a protective coating.…”
Section: -Specific Combinationsmentioning
confidence: 99%
“…Metallurgically, such LMCs pose less of a challenge at their interface with iron and its alloys than do aluminium alloys: Refs. [17,22,23] give examples of interfacial engineering in magnesium-steel LMCs produced by reactive transient liquid phase bonding, or by pressure infiltration, respectively. On the other hand the wet corrosion resistance of this LMC is dismal: to be usable it must be completely sealed from the environment with a protective coating.…”
Section: -Specific Combinationsmentioning
confidence: 99%
“…The bondability of AZ31 to low carbon steel with the addition of Ag interlayer using rTPL process showed that isothermal solidification of the eutectic melt was formed at the Mg alloy side through the diffusion of Ag into the magnesium BM. Thin and uniform Fe 2 Al 5 layer was observed at the steel side, which significantly improved the joint strength to 201 MPa [44,81]. In contrast, coarse, non-uniform IMC intermittently formed at the interface without Ag interlayer, which deteriorates the joint performance.…”
Section: Diffusion and Eutectic Bondingmentioning
confidence: 99%
“…The number of research suggested that interfacial bonding could be achieved by either addition of interlayer or some alloying elements in the Mg BM. The benefits of using Cu [78][79][80], Ni [37,80], and Ag [44,81] interlayers during diffusion bonding of Mg alloy/steel have been demonstrated.…”
Section: Diffusion and Eutectic Bondingmentioning
confidence: 99%
See 2 more Smart Citations